2000
DOI: 10.4319/lo.2000.45.6.1274
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of ultraviolet radiation in mountain lakes: Factors controlling the among‐ and within‐lake variability

Abstract: High-altitude lakes are exposed to high fluence rates of solar ultraviolet radiation (UVR; 290-400 nm) and contain low concentrations of dissolved organic carbon (DOC). While in most lowland lakes, DOC can be used to predict UV transparency with sufficient accuracy, current models fail to estimate UVR in clear alpine lakes. In these lakes, phytoplankton may contribute significantly to the UV attenuation either as particles or as a source of chromophoric dissolved organic matter (CDOM) with distinctive properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
280
3
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 259 publications
(307 citation statements)
references
References 58 publications
(77 reference statements)
18
280
3
6
Order By: Relevance
“…On the other hand, negligible R T* was observed in the case of Lago Rouen, which is mostly surrounded by exposed rocks. Such an environment is expected to decrease the importance of soil runoff as organic matter source (Laurion et al, 2000). Soil-derived organic matter usually includes a considerable fraction of humic substances (Vinebrooke and Leavitt, 1998) with significant photochemical activity (Halladja et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, negligible R T* was observed in the case of Lago Rouen, which is mostly surrounded by exposed rocks. Such an environment is expected to decrease the importance of soil runoff as organic matter source (Laurion et al, 2000). Soil-derived organic matter usually includes a considerable fraction of humic substances (Vinebrooke and Leavitt, 1998) with significant photochemical activity (Halladja et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…A combination of altitude and low concentration of UV-absorbing substances favours the penetration of harmful UV radiation in the water column (Laurion et al, 2000). Despite the development of several adaptations by aquatic organisms (Sommaruga, 2010), alpine lakes are a potentially vulnerable environment to climate change because of the possible increase of UV doses connected to variations in organic matter inputs and, most notably, to decreases in ice cover (Neale et al, 2001; Leavitt et al, 2003;Rogora et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A shoulder value was found at approximately 275 nm [a CDOM (275 nm)] in Taihu lake (Bidigare, 1989;Laurion et al, 2000;Bontempi et al, 2004;Repetad et al, 2004;Kieber et al, 2007), which also appeared in the data of Zhao and Qin (2008) and Warnock and Gieskes (1999). This shoulder value destroys the consistency of CDOM exponential decrease with wavelength.…”
Section: Effect Of Components On Absorption Coefficient Of Chromophormentioning
confidence: 87%
“…However, there is slight fluctuation at approximately 334 nm in this study. A flat peak, which might be associated with the absorption by proteins and nucleic acids (Bidigare, 1989;Laurion et al, 2000), was found at approximately 275 nm. There may be two reasons for this: first, there were small numbers of phytoplankton in studied water; second, damage of phytoplankton cell was avoided by using low pressure during filtration.…”
Section: Chromophoric Dissolved Organic Matter Absorptionmentioning
confidence: 99%
“…Changes in DOC concentration are important because they affect the penetration of sunlight (and most notably of UV radiation) into the water column (Laurion et al, 2000), as well as several other processes including photochemical reactions (Schindler, 1997).…”
Section: Introductionmentioning
confidence: 99%